Male Homosexual Preference: Femininity and the Older Brother Effect in Indonesia. (14th November 2019) - Nila, Sarah; Crochet, Pierre-Andre; Barthes, Julien; Rianti, Puji; Juliandi, Berry; Suryobroto, Bambang; Raymond, Michel
Male homosexual preference (MHP) is an evolutionary enigma because it is partially heritable and imposes a fertility cost. In occidental societies, homosexual men are feminized at various levels and they have more older brothers than heterosexual men. To evaluate whether femininity and the fraternal birth order (FBO) effect are universal features of MHP or not, we collected original data from homosexual men, heterosexual men, and heterosexual women from Java (Indonesia). Facial photographs were used to test whether homosexual faces are feminized when compared with heterosexual ones. We found that faces manipulated to resemble the average face of homosexual men are perceived as facially feminized, suggesting that homosexual men are facially feminized compared to heterosexual men, although a higher facial femininity was not captured by morphological analyses. Then, family data were used to detect differences in siblings' composition between homosexuals and heterosexuals. Homosexual men displayed a higher number of older brothers than heterosexual men, even when sibship size was controlled for, suggesting that the FBO effect exists in Indonesian populations. Independent of sexual orientation, men with older brothers seem more feminized than those without older brothers, consistent with the immune origin of the FBO effect. In conclusion, MHP in Indonesia is partially feminized and they have more older brothers. Such features are also associated with MHP in other cultural contexts, suggesting a cross-cultural effect of men homosexual preference. An evolutionary explanation is available for the feminizing effect, although the FBO effect remains unexplained even if proximal mechanisms start to be identified.